Freeze-out purifier for helium refrigeration system applications. Issue 1 (March 2020) - Kroll, D; Hasan, N; Ganni, V; Fila, A; Engeda, A
Abstract: Purification systems are necessary to support commissioning and operation of helium refrigeration and associated experimental systems. These systems are typically designed for a low level of impurity (i.e., in parts per million), since a 4.5 K or 2 K helium system will solidify, or freeze out every other substance. The trace impurities can block and/or change the flow distribution in heat exchangers and potentially damage turbines or cryogenic compressors operating at high speed. Experimental systems, such as superconducting magnets, require helium purification due to inherent characteristics in their construction. These are also used for the commissioning of sub-systems, like the compressors, and cold boxes. As known from experience, molecular sieves do not remove low-level moisture impurity sufficiently. Typical commercial freeze-out purifiers using molecular sieves have very short operating times between regeneration and are inefficient requiring substantial utilities like liquid nitrogen and high-pressure operation. Based upon proven experience from a freeze-out purifier design for Brookhaven National Lab (BNL) in 1983, a liquid nitrogen assisted freeze-out purifier has been designed. This design includes a multi-pass and multi-stream heat exchanger and an activated carbon bed. The heat exchanger design is expected to minimize the liquid nitrogen usage and extend the capacity and the operating pressure range, thereby the time interval between regeneration. The goal is to provide a simple design procedure to develop and operate an efficient purifier system.